Political Philosophy of Prophet Yusuf in Qur’an: A Multi-Disciplinary Approach - Nuriz, M Adib Fuadi; Amrullah, Khasib; Hidayatullah, Rakhmad Agung; Khakim, Usmanul; Anggara, Deki Ridho Adi (AL QUDS : Jurnal Studi Alquran dan Hadis, 2024)
The narrative around the prophet Yusuf is widely regarded as the preeminent story due to its wealth of life teachings, including those pertinent to politics. It is noteworthy that an apostle who ascends to a position of authority in a powerful nation does so from a subordinate position rife with restrictions and capable of involvement in political affairs with the nubuwah attributes associated with such a post. In the range of non-ideal politics today, it is imperative to delve into the prophet Yusuf's political dimensions to provide a valuable resource for political scholars and professionals. The life narrative of the prophet Yusuf and the social dimensions that encompass it are inseparable; thus, this investigation will encompass, to the necessary extent, a variety of disciplines, including tafseer, law, social sciences, psychology, history, economics, management, epistemology, and political philosophy, which is the most prominent. Consequently, the objective of this paper is to expound upon the prophet Yusuf's political theory as elucidated in Surat Yusuf via the lens of multiple academic disciplines. This research is a literature review in which qualitative content analysis is utilized to analyze the data. The results of this study are: Initially, the prophet Yusuf's political career encountered obstacles at the level of family, community, and the center of state. Secondly, the prophet Yusuf's integrity and dedication to the truth, as well as his political acumen, knowledge, and wisdom (God). Furthermore, the stability of a nation is ensured by economic resilience and legal fairness.